الرضا عن الشعبة الدراسية و علاقته بالتحصيل الدراسي لدى تلاميذ السنة الثانية ثانوي دراسة ميدانية بالاغواط - بوشريط ايمان; قوقة خيرة; داودي محمد (My University, 2023)
The current study aimed to identify the relationship between satisfaction with the academic discipline and academic achievement among a sample of second year secondary students in the city of Laghouat. Where the study was applied to a sample of (48) male and female students from the second year secondary school students (11) males and (37) females. For the first season and the second season . The study reached the following results: 1_ The level of satisfaction with the study section, among second year secondary school students, is high. 2_ The level of academic achievement of second year secondary school students is high. 3_ There is a direct correlation between satisfaction with the academic section and academic achievement. 4_ There are no statistically significant individual differences in the degrees of satisfaction with the study section of second year secondary students due to gender. 5_ There are no statistically significant differences in the degrees of satisfaction with the academic division due to the type of academic division. Keywords: Satisfaction with the academic section, academic achievement